PERANCANGAN GELAGAR BETON BERTULANG BALOK-T JEMBATAN NON-STANDAR LEBAR 6 METER DENGAN PERATURAN RSNI T-02-2005 - , YOSEPHIN NUKE C M; , Dr. âIng. Ir. Djoko Sulistyo ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this modern era, transportation is one of the basic necessities of the society. Lack of transportation facility could be the cause of poverty. In rural areas, those lacks of necessities is still often found, such as broken roads, bridges, and very simple pedestrian bridges. Thus, infrastructures are needed for connecting between rural and urban areas, like bridges. They donât need to be wide, but strong enough for big trucks like agriculture trucks or logistic trucks to cross over. But, the existed Reinforced T-Beam Concrete Bridge only provides the profile design for 9 meters width Bridge, which is inefficient for rural areas. So the non-standard bridge design could become a solution to overcome these transportation necessities. This nonstandard bridgeâs design is limited for single lane bridge with the total width of 6 m including sidewalk. The purpose of this T-beam girder reinforced concrete bridge design is to design and analyze the bridge profile dimension and reinforcement. The design starts by determining bridge profiles which is typical with profiles in Standar Jembatan Gelagar Beton Bertulang Balok T Tahun 1997, then analyze bridge loads, design reinforcements, then analyzing and comparing with bridge strength. The result shows that the profile dimensions and reinforcement needs for standard bridge is appropriate with the non-standard bridge design with changing the reinforcement quality form 295 MPa to 390 MPa. But the shear reinforcements which the standard use is 10 mm reinforcement with yield strength 240 MPa need to be changed into 12 mm with yield strength 320 MPa. This quality changing is made to suit the reinforcement quality that available on market nowadays. Meanwhile, the standardâs floor plate reinforcement is 12 mm, but the designâs result shows that it needed to be larger. The analysis shows that the non-standard bridge girder could support the bridge loads.